Preliminary study on the mechanisms of ankle injuries under falling and impact conditions based on the THUMS model - Zhengdong Li; Jianhua Zhang; Jinming Wang; Ping Huang; Donghua Zou; Yijiu Chen (Oxford University Press, 2021)
Ankle injuries are common in forensic practice, which are mainly caused by falling and traffic accidents. Determining the mechanisms and manners of ankle injuries is a critical and challenging problem for forensic experts. The identification of the injury mechanism is still experience-based and strongly subjective. There also lacks systematic research in current practice. In our study, based on the widely used Total Human Model of Safety 4.0 (THUMS 4.0), we utilized the finite element (FE) method to simulate ankle injuries caused by falls from different heights (5 m, 10 m and 20 m) with different landing postures (natural posture, inversion, eversion, plantar-flexion and dorsi-flexion) and injuries caused by impacts from different directions (anterior-posterior, lateral-medial and posterior-anterior) with different speeds (10 m/s, 15 m/s and 20 m/s) at different sites (ankle and lower, middle and upper sections of leg). We compared the injury morphology and analyzed the mechanisms of ankle injuries. The results showed that falling causes a specific compression fracture of the distal tibia, while fractures of the tibia and fibula diaphysis and ligament injuries caused by falling from a lower height or inversion, planter flexion or dorsiflexion at a large angle are not distinguishable from the similar injury patterns caused by impact on the middle and upper segments of the leg. No obvious compression fracture of the tibia distal was caused by the impacts, whereas ligament injuries and avulsion fractures of the medial or lateral condyle and fractures of the diaphysis of the tibia and fibula were observed. Systematic studies will be helpful in reconstructing the ankle injury processes and analyzing the mechanisms in forensic practice, providing a deeper understanding of ankle injury mechanisms for forensic experts.